Cerebral venous thrombosis secondary to hyperthyroidism: A case report - Pant, Basant; Bajracharya, Malika; Chandra, Avinash; Bati, Ramita; Rajbhadari, Reema; Acharya, Sameer; Shrestha, Pranaya; Shrestha, Resha; Rajbhandari, Pravesh; Bhattarai, Robin (Nepal Journal of Neuroscience, 2018)
Cerebral Venous Thrombosis (CVT) is a rare form of Stroke characterized by thrombus formation in the cerebral veins. CVT is a result of various reasons among which the hyperthyroidism is not so frequently encountered. This is probably the first case report published from Nepal. The aim of this case report is to give the message that persistent severe headache in patient with hyperthyroidism can be the red flag and needs to be investigated further. We present a case of a 35 years old female who presented with complaints of severe headache and persistent in nature associated with vomiting since 5 days. She was a diagnosed subacute thryroiditis and under medicine from 1 month before presenting to us. Her Magnetic Resonance Venography (MRV) brain showed venous thrombosis within superior saggital sinus, left transverse sinus and sigmoid sinus. Her thyroid function test showed pretreatment T3 of 2.98 ng/ml T4 of 1.02 mg/ ml and TSH of 0.12 μIU/L. She was kept on anticoagulants and other supportive measures. The patient showed improving status with the conservative management. Nepal Journal of Neuroscience 15:29-31, 2018